HIJAUAN LOKAL, GIZI GLOBAL: EDUKASI PEMANFAATAN LEGUMINOSA DALAM MENINGKATKAN KETAHANAN PAKAN KAMBING - Amalyadi, Rezki (Jurnal Media Pengabdian Kepada Masyarakat, 2025)
Goat farming in Teruwai Village, Pujut Subdistrict, Central Lombok Regency, plays an important role in supporting family economies and local food security. However, the low availability of quality feed, especially during the dry season, is a major challenge that affects livestock productivity and health. Despite this, the area has untapped potential in local forage crops such as leguminous plants like lamtoro and gamal. This community service initiative aims to enhance farmers' capabilities through technical education and field training on the cultivation and utilisation of leguminous plants as alternative feed. A participatory approach was employed, involving the ‘Tunas Karya II’ farmers' group. Evaluation results showed an increase in farmers' knowledge and changes in feeding behaviour, with 76% of members beginning to regularly mix leguminous plants into their daily rations. This activity proved effective in addressing farmers' needs for sustainable feed solutions and has the potential to be replicated in other regions with similar conditions.